2012
DOI: 10.1515/gmj-2012-0028
|View full text |Cite
|
Sign up to set email alerts
|

Global nonexistence and stability of solutions of inverse problems for a class of Petrovsky systems

Abstract: In this work, we find conditions on data guaranteeing the global nonexistence of solutions to inverse source problems for a class of Petrovsky systems. We also establish asymptotic stability results for the corresponding problems with the opposite sign of power-type nonlinearities and the integral constraint vanishing as time tends to infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Wu and Tsai [31] considered (1.4) and proved that the solution is global in time under some conditions without the relation between m and p. Moreover, similar to [16], they proved that if p > m, the local solution blows up in finite time. (see also [9,27])…”
Section: Case Of Constant Exponentsmentioning
confidence: 99%
“…Wu and Tsai [31] considered (1.4) and proved that the solution is global in time under some conditions without the relation between m and p. Moreover, similar to [16], they proved that if p > m, the local solution blows up in finite time. (see also [9,27])…”
Section: Case Of Constant Exponentsmentioning
confidence: 99%
“…For more information about the concavity argument, we refer the readers to [16][17][18]. In [26] Shahrouzi and Tahamtani by using the same method found conditions on data that guaranteeing the global nonexistence and asymptotic stability results for a class of Petrovsky inverse source problems (see also [22][23][24]27]). Bukhge ǐm et al [7] considered an inverse problem for the stationary elasticity system with constant Lamé coefficients and variable matrix coefficient depending on the spatial variables and frequency.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Tahamtani and Shahrouzi studied asymptotic behavior of solutions for the following inverse problem: utt+Δ2uα1Δu+α2ut+α3|u|pu+b(x,t,u,u,Δu)=f(t)ω(x),xΩ,t>0, u(x,t)=0,Δu=c0νu(x,t),xΓ,t>0, u(x,0)=u0(x),ut(x,0)=u1(x),xΩ, Ωu(x,t)ω(x)dx=ϕ(t),t>0, and showed that the solutions of this problem under some appropriate conditions are stable if α 1 and α 2 being large enough, α 3 ≥0 and ϕ ( t ) tend to zero as time goes to infinity and established a blow‐up result, if α 3 <0 and ϕ ( t ) = k be a constant. For more information about inverse problems, we refer the readers to the works in .…”
Section: Introductionmentioning
confidence: 99%